Energy and electricity consumption analysis of Malaysian industrial sector - Saidur, R.; Husnawan, M.; Masjuki, Haji Hassan; Jahirul, M.I.; Mahlia, T.M.I.; Nasruddin, A.R.; Mekhilef, Saad; Ping, H.W.; Zamaluddin, M.F. (2009)
Malaysia has been experiencing strong economic growth through the last decade. Energy has been a key input in the development and growth of the country. The industrial sector is the second largest consumers of energy in Malaysia. In the present work sixty-four (64) factories in seven different manufacturing sectors were audited within the four regions of east-coast of Malaysia. In this audit, the most important parameters that have been collected are; power rating and operation time of energy consuming equipment/machinery; fossil fuel and other sources of energy consumption; production figure; peak and off peak tariff usage behavior; and power factor. These data were analyzed to investigate the breakdown of end-use equipment/machinery, the peak and off peak usage behavior, power factor trend, specific energy consumption and specific electricity consumption. The result of the energy audit shows that the highest energy consuming equipment is electric motor followed by liquid pumps and air compressor. The highest specific total energy (fossil fuel and electricity) consumption among the industrial sub-sectors is found in the rubber producing industries followed by fabricated metal industries, while the highest specific electrical energy consumption was found in the fabricated metal industries followed by rubber producing industries. The specific energy and electricity consumptions found in the present study are compared with Indonesian industrial sectors and presented in thin paper. The study also found that the 64% electrical energy was consumed in peak hours by the industries and average power factor ranged from 0.88 to 0.91. The energy audit in this study can be important tools and approaches for the policy maker to get insight into the energy and electricity uses pattern of Malaysian industrial sector.